2022
DOI: 10.4081/ija.2022.2025
|View full text |Cite
|
Sign up to set email alerts
|

Organic spelt production systems: Productive and financial performance in three orographic regions

Abstract: A two-year field trial was conducted to study the effects of biohumus, biofertiliser, and soil conditioner application on spelt grain yield in different regions (plain, hilly, and mountainous regions) in Serbia. An analysis of economic efficiency indicators of spelt production in organic farming systems was also performed. The field experiment had a randomised complete block design with three replicates in each of the three regions. One winter spelt cultivar was also studied. The largest differences in spelt y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although organic spelt already occupies a niche market in North America and Europe [15], there are still many opportunities for organic or small-scale farms to offer minimally processed spelt products, such as whole grains and groats. Dolijanović et al [11] reported significant differences in organic spelt production between different regions, i.e., lowland, hilly, and mountainous. Significantly higher protein contents were reported for spelt than for common wheat, but there were no differences between conventional and organic farming systems [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although organic spelt already occupies a niche market in North America and Europe [15], there are still many opportunities for organic or small-scale farms to offer minimally processed spelt products, such as whole grains and groats. Dolijanović et al [11] reported significant differences in organic spelt production between different regions, i.e., lowland, hilly, and mountainous. Significantly higher protein contents were reported for spelt than for common wheat, but there were no differences between conventional and organic farming systems [1].…”
Section: Discussionmentioning
confidence: 99%
“…Spelt (Triticum spelta L.) is an ancient hulled wheat that has attracted new interest in recent years because it is a low-input crop suitable for pesticide-free cultivation in organic farming systems [10]. The disadvantages of spelt cultivation are its high susceptibility to lodging, because the plants are much taller compared with wheat, and the additional step of hulling the grains after harvest [11]. Spelt grains are covered by tough glumes, which protect the grains from external influences, but cause difficulties in harvesting and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Government, non-government organizations (NGOs), and farmer groups conduct counseling, training, demonstration plots, and field schools to promote organic farming knowledge. The awareness to move to organic is a result of farmers' desire to attain healthy products, maintain rich soil, and minimize expenditure on fertilizers and pesticides [43] owing to lower government subsidies. With RMS values of 5.02 and 4.79, respectively, the leverage analysis disclosed that the experience of organic paddy farming and the availability of organic paddy farming infrastructure were sensitive variables for enhancing the social sustainability status.…”
Section: Sustainability Status Of Organic Paddy Farmingmentioning
confidence: 99%
“…In addition, the conversion area has been limited to planting with traditional land, resulting in relatively high water pollution and inorganic inputs. The water supply is sourced from the same irrigation water, causing relatively high chemical contamination [43,46].…”
Section: Sustainability Status Of Organic Paddy Farmingmentioning
confidence: 99%
“…Spelt ( Triticum spelta L.) is an ancient hulled wheat that has attracted new interest in recent years because it is a low-input crop suitable for pesticide-free cultivation in organic farming [ 17 ]. The disadvantage of spelt cultivation is the lodging of the plants and the need to hull the grains after harvest [ 18 ]. Spelt grains are covered with a strong chaff, which protects them from external harmful influences but makes harvesting and processing difficult.…”
Section: Introductionmentioning
confidence: 99%